Infrared absorbing film and preparation method thereof
By using polyester resin, modified resin and infrared absorbing masterbatch (KxWO3 and modified CsyWO3), the problem of insufficient heat resistance and mechanical properties of existing materials is solved, and efficient infrared absorption and good long-term stability is achieved.
Patent Information
- Application Number
- CN202411091718.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The heat resistance and mechanical properties of existing infrared absorbing materials are insufficient, and the infrared absorption rate is not high, and the long-term use performance is degraded.
Infrared absorption films are prepared by melt extrusion through a twin-screw extruder using components such as polyester resin, modified resin and infrared absorbing masterbatch (composed of KxWO3 and modified CsyWO3).
It achieves the maximum infrared absorption performance without sacrificing visible light transmittance, and has excellent heat resistance and mechanical properties, and has excellent long-term stability.
Smart Images

Figure BDA0004986761510000111 
Figure BDA0004986761510000112
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of infrared absorbing materials, and in particular relates to an infrared absorbing film and a preparation method thereof. Background Art
[0002] In recent years, with the increasing interest in environmental and energy-related issues, glass films for heat insulation and energy saving have gradually attracted people's attention. They are not only used for automobile glass films, but also for architectural glass windows. This kind of glass film needs to have the characteristics of transmitting visible light and shielding infrared light, that is, it needs to ensure the heat insulation effect under certain visible light transmittance conditions, while reducing the transmittance of the infrared light band (780-2500nm) in the sunlight spectrum as much as possible.
[0003] At present, the infrared absorption materials used in films at home and abroad mainly include: silicon carbide, silicon nitride nanopowder, cobalt nickel nanopowder, nanographite, Fe, Co, Ni and other nanometals and alloys, nanometal oxides, nanoneedle-shaped magnetic metal powders, etc. Among them, the unique structure of nanometal oxides gives them unique properties and advantages in infrared absorption materials, but nanooxide powders are easy to agglomerate and difficult to disperse evenly, and their infrared absorption performance is unstable, and the performance is significantly reduced in long-term use.
[0004] Patent CN201711396606 discloses a thermoplastic polyurethane elastomer (TPU) film with infrared absorption function and its preparation method. Infrared absorbing substances polyaniline and polypyrrole are mixed and extruded with polycarbonate, polyvinyl pyrrolidone, TPU particles, and nano-silicon dioxide to obtain a TPU film. The film has good flexibility and mechanical properties, but the physical mixing has the problem of uneven dispersion of infrared absorbing substances, and the infrared absorption rate is only 60-75%. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an infrared absorbing film and a method for preparing the same, wherein the film has excellent heat resistance and mechanical properties, and can achieve maximum infrared absorption performance without sacrificing visible light transmittance, while having excellent long-term stability.
[0006] In order to achieve the above object, according to one aspect of the present invention, an infrared absorbing film is provided, comprising the following components in parts by weight: 100-110 parts of polyester resin, 10-20 parts of modified resin, 20-35 parts of infrared absorbing masterbatch, and 4-17 parts of other additives; wherein the infrared absorbing masterbatch, calculated on a total weight percentage of 100%, comprises the following raw material components: 55-75% of carrier resin, 10-15% of K x WO3 and 15-30% modified Cs y WO3; wherein 0<x<1, 0<y<1; the Kx WO3 and the modified Cs y The mass ratio of WO3 is 1:1.5-2.
[0007] In some embodiments, the polyester resin and the carrier resin are each independently selected from one or more of polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate.
[0008] In some embodiments, the modified resin is polyethylene naphthalate, and the intrinsic viscosity of the polyethylene naphthalate is 0.65-0.80 dL / g.
[0009] In some embodiments, the modified Cs y WO3 is Cs coated with polyvinyl pyrrolidone y WO3; the modified Cs y In WO3, the mass proportion of polyvinyl pyrrolidone is 3-5%.
[0010] In some embodiments, the other auxiliary agents include any one or more of an antioxidant, an ultraviolet light absorber, and a lubricant.
[0011] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned infrared absorbing film, comprising the following steps:
[0012] (1) Preparation of infrared absorption masterbatch: Tungsten chloride and potassium acetate were added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, and centrifuged and dried after the reaction to obtain the K x WO3; Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3; the K x WO3, the modified Cs y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the infrared absorbing masterbatch;
[0013] (2) The infrared absorbing masterbatch, polyester resin, modified resin and other additives in step (1) are uniformly mixed in proportion, sent to a twin-screw extruder for melt mixing, and then extruded into a film to obtain the infrared absorbing film.
[0014] In some embodiments, in step (1), the concentration of tungsten chloride in ethanol is 13-15 mg / mL.
[0015] In some embodiments, in step (1), the Cs y The mass ratio of WO3 to polyvinyl pyrrolidone is 100:6-10.
[0016] In some embodiments, in step (2), the extrusion temperature is 270-290° C., and the extrusion pressure is 4-6 MPa.
[0017] According to another aspect of the present invention, there is also provided a use of the infrared absorbing film or the infrared absorbing film prepared according to the preparation method in glass film.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention firstly converts K x WO3 and modified Cs y WO3, and further find the optimal addition ratio of the two substances to prepare an infrared absorption masterbatch with excellent performance, and then add the masterbatch to the polyester resin and a certain amount of modified resin to obtain an infrared absorption film. The film has excellent heat resistance and mechanical properties, and can achieve maximum infrared absorption performance without sacrificing visible light transmittance, and has excellent long-term stability.
[0020] (2) The preparation method of the infrared absorbing film of the present invention is simple and has good application prospects. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0023] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0025] In the present invention, the intrinsic viscosity test standard is GB / T14190-2008.
[0026] The present invention provides an infrared absorbing film, comprising the following components: polyester resin, modified resin, infrared absorbing masterbatch and other additives. In the present invention, the thickness of the infrared absorbing film is 0.02-0.06 mm. It can be understood that the thickness can be any specific value of 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm or any value within the range of 0.02-0.06 mm.
[0027] In the present invention, the weight of the polyester resin is 100-110 parts. It can be understood that the weight can be any specific value of 100 parts, 101 parts, 102 parts, 103 parts, 104 parts, 105 parts, 106 parts, 107 parts, 108 parts, 109 parts, 110 parts or any value within the range of 100-110 parts. In some embodiments, the polyester resin is selected from one or more of polyethylene terephthalate, polypropylene terephthalate, and polybutylene terephthalate.
[0028] In the present invention, the weight of the modified resin is 10-20 parts. It is understood that the weight of the modified resin can be any specific value of 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, and 20 parts, or any value within the range of 10-20 parts. In some embodiments, the modified resin is polyethylene naphthalate, and the intrinsic viscosity of the polyethylene naphthalate is 0.65-0.80dL / g. In the present invention, the intrinsic viscosity is the viscosity measured at 25°C by dissolving the sample in a mixed solvent with a weight ratio of phenol to tetrachloroethane of 1:1 using an Ubbelohde viscometer. The present invention mixes a polyester resin with a small amount of modified resin, and further finds the optimal mixing ratio of the two, so that the obtained film has excellent mechanical properties, heat resistance and optical properties. If the content of the modified resin is too low, the heat resistance and mechanical properties will be insufficient; if the content of the modified resin is too high, the flexibility of the film will deteriorate.
[0029] In the present invention, the weight percentage of the infrared absorbing masterbatch is 20-35 parts. It can be understood that the weight percentage can be any specific value of 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts or any value within the range of 20-35 parts. In some embodiments, the infrared absorbing masterbatch, calculated as a total mass percentage of 100%, includes the following raw material components: 55-75% of carrier resin, K x WO310-15% and modified Cs y WO315-30%; wherein 0<x<1, 0<y<1. In some embodiments, x=0.3, y=0.33. In some embodiments, the K x WO3 and the modified Cs y The mass ratio of WO3 is 1:1.5-2. It is understandable that the mass ratio can be any specific value of 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or any value within the range of 1:1.5-2. x WO3 and the modified Cs y The mass ratio of WO3 can further regulate the comprehensive optical properties of the masterbatch, maximize the synergistic effect of the two substances, and achieve maximum infrared absorption performance without sacrificing visible light transmittance.
[0030] In the present invention, in the infrared absorbing masterbatch, the mass fraction of the carrier resin is 55-75% based on the total mass percentage of 100%. It can be understood that the mass fraction can be any specific value of 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, or any value within the range of 55-75%. In some embodiments, the carrier resin is selected from one or more of polyethylene terephthalate, polypropylene terephthalate, and polybutylene terephthalate.
[0031] In the present invention, in the infrared absorbing masterbatch, based on the total mass percentage of 100%, the K x The mass fraction of WO3 is 10-15%. It is understood that the mass fraction can be any specific value of 10%, 11%, 12%, 13%, 14%, 15%, or any value within the range of 10-15%. In some embodiments, the K x The average aspect ratio of WO3 is 13-15. xWO3 can ensure a higher carrier concentration, thereby improving infrared absorption performance.
[0032] In the present invention, in the infrared absorbing masterbatch, based on the total mass percentage of 100%, the modified Cs y The mass fraction of WO3 is 15-30%. It is understood that the mass fraction can be any specific value of 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or any value within the range of 15-30%. In some embodiments, the modified Cs y WO3 is Cs coated with polyvinyl pyrrolidone on the outside. y WO3; the modified Cs y In WO3, the mass proportion of polyvinyl pyrrolidone is 3-5%. In some embodiments, the modified Cs y The particle size of WO3 is 140-160nm. It can be understood that the particle size can be any specific value of 140nm, 142nm, 144nm, 146nm, 148nm, 150nm, 152nm, 154nm, 156nm, 158nm, 160nm or any value within the range of 140-160nm.
[0033] The present invention uses a specific content of polyvinyl pyrrolidone to modify Cs y WO3, and further adjusted the modified Cs y The mass proportion of polyvinyl pyrrolidone in WO3 and the obtained modified Cs y WO3 can take into account both long-term dispersion stability and excellent infrared absorption performance. y The mass proportion of polyvinyl pyrrolidone in WO3 is relatively low, so the dispersion stability is not significantly improved; if the modified Cs y The mass proportion of polyvinyl pyrrolidone in WO3 is relatively high, the dispersion stability will be reduced, and the infrared absorption performance will also be significantly reduced.
[0034] In the present invention, the weight proportion of the other auxiliary agents is 4-17 parts, preferably 5-15 parts. In some embodiments, the other auxiliary agents include any one or more of antioxidants, ultraviolet light absorbers, and lubricants. In some embodiments, the weight proportion of the antioxidant is 1-5 parts; in some embodiments, the antioxidant is a compound of antioxidant 1010 and antioxidant 168, and the compounding ratio of the two is 1:1-2. In some embodiments, the weight proportion of the ultraviolet light absorber is 1-5 parts; in some embodiments, the ultraviolet light absorber is a benzotriazole ultraviolet light absorber. In some embodiments, the weight proportion of the lubricant is 2-7 parts; in some embodiments, the lubricant includes one or more of stearic acid, pentaerythritol ester, oxidized wax, white oil, zinc stearate, and calcium stearate.
[0035] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned infrared absorbing film, comprising the following steps:
[0036] (1) Preparation of infrared absorption masterbatch: Tungsten chloride and potassium acetate were added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, and centrifuged and dried after the reaction to obtain the K x WO3; Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3; the K x WO3, the modified Cs y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the infrared absorbing masterbatch;
[0037] (2) The infrared absorbing masterbatch, polyester resin, modified resin and other additives in step (1) are uniformly mixed in proportion, sent to a twin-screw extruder for melt mixing, and then extruded into a film to obtain the infrared absorbing film.
[0038] In the present invention, in step (1), tungsten chloride and potassium acetate are added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, and centrifuged and dried after the reaction to obtain the K x WO3. In some embodiments, in step (1), the concentration of tungsten chloride in ethanol is 13-15 mg / mL. The present invention can effectively control the obtained K by controlling the concentration of tungsten chloride. x The microscopic size of WO3 ensures K x WO3 and modified Cs yEffective synergy of WO3.
[0039] In the present invention, in step (1), Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3. In the present invention, the ethanol solution of polyvinyl pyrrolidone refers to a solution obtained by dissolving a certain amount of polyvinyl pyrrolidone in a certain amount of ethanol. In some embodiments, the ball milling time may be 2-4 hours. In some embodiments, the stirring time may be 1-2 hours. In some embodiments, the ultrasonic treatment time may be 0.5-1 hour. In some embodiments, the Cs y The mass ratio of WO3 and polyvinyl pyrrolidone is 100:6-10. It can be understood that the mass ratio can be any specific value of 100:6, 100:6.5, 100:7, 100:7.5, 100:8, 100:8.5, 100:9, 100:9.5, 100:10 or any value within the range of 100:6-10.
[0040] In the present invention, in step (1), the K x WO3, the modified Cs y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the infrared absorption masterbatch. In some embodiments, the rotation speed of the twin-screw extruder is 100-500r / min. It can be understood that the rotation speed can be any specific value of 100r / min, 150r / min, 200r / min, 250r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min or any value within the range of 100-500r / min. In some embodiments, the temperature of each zone of the screw of the twin-screw extruder is 180-230°C. It can be understood that the temperature can be any specific value of 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C or any value within the range of 180-230°C.
[0041] In the present invention, in step (2), the infrared absorbing masterbatch, polyester resin, modified resin and other additives are mixed uniformly in proportion, sent to a twin-screw extruder for melt mixing, and then extruded into a film to obtain the infrared absorbing film. In some embodiments, the extrusion temperature is 270-290°C. It can be understood that the temperature can be any specific value of 270°C, 275°C, 280°C, 285°C, 290°C or any value within the range of 270-290°C. In some embodiments, the extrusion pressure is 4-6MPa.
[0042] According to another aspect of the present invention, there is also provided application of the infrared absorbing film or the infrared absorbing film prepared according to the preparation method in glass film.
[0043] The present invention will be described in detail below by way of examples. It should be understood that the following examples are only used to further explain and illustrate the content of the present invention by way of example, and are not intended to limit the present invention.
[0044] Unless otherwise specified, the raw materials in the examples and comparative examples of the present invention are all commercially available, and the specific information is as follows:
[0045] Polyethylene terephthalate: intrinsic viscosity is 0.65 dL / g, purchased from Teijin of Japan; Polybutylene terephthalate: intrinsic viscosity is 0.9 dL / g, purchased from Toray Industries, Ltd.; Modified resin: polyethylene naphthalate, intrinsic viscosity is 0.75 dL / g, purchased from Teijin of Japan; Polyvinyl pyrrolidone: purchased from Beijing Bailingwei Technology Co., Ltd.; Tungsten chloride, potassium acetate, ethanol: purchased from Aladdin; Cs y WO3: 30-50nm, y=0.33, purchased from Zhejiang Zhiti Nano New Materials Co., Ltd.; Antioxidant: a mixture of antioxidant 1010 and antioxidant 168, with the mixture ratio of 1:1; Ultraviolet light absorber: Ultraviolet light absorber UV-326, purchased from Nanjing Hualiming Chemical Co., Ltd.; Lubricant: stearic acid, purchased from Aladdin.
[0046] Example 1
[0047] The infrared absorption film of this embodiment comprises the following components in parts by weight: 100 parts of polyethylene terephthalate, 10 parts of polyethylene naphthalate, 20 parts of infrared absorption masterbatch, 5 parts of antioxidant, 4 parts of ultraviolet light absorber, and 5 parts of lubricant; wherein the infrared absorption masterbatch comprises the following raw material components based on the total mass percentage of 100%: 70% polyethylene terephthalate, 10% K x WO3 and 20% modified Cs y WO3; wherein x=0.3, y=0.33.
[0048] The method for preparing the infrared absorbing film described in this embodiment comprises the following steps:
[0049] (1) 8 g of tungsten chloride and 0.1 g of potassium acetate were added to 0.6 L of ethanol, ultrasonicated and stirred until fully dissolved, reacted at 180° C. for 24 h, centrifuged after the reaction, and dried at 60° C. for 24 h to obtain the K x WO3; 100gCs y WO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 10 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 24 h to obtain the modified Cs y WO3; 5g of K x WO3, 10g of the modified Cs y WO3 and 35g polyethylene terephthalate are mixed evenly and then sent to a twin-screw extruder for melt extrusion granulation. The speed of the twin-screw extruder is 500r / min. The extrusion temperatures in the screws of the twin-screw extruder are: 180-190°C in zone 1, 190-210°C in zone 2, 190-210°C in zone 3, 190-210°C in zone 4, 210-230°C in zone 5, and dried at 70°C to obtain the infrared absorption masterbatch.
[0050] (2) 20 g of the infrared absorbing masterbatch described in step (1), 100 g of polyethylene terephthalate, 10 g of polyethylene naphthalate, 5 g of antioxidant, 4 g of ultraviolet light absorber, and 5 g of lubricant are mixed uniformly, sent to a twin-screw extruder for melt mixing, and extruded into a film at a temperature of 290° C. and a pressure of 4 MPa to obtain the infrared absorbing film.
[0051] Example 2
[0052] The infrared absorption film of this embodiment comprises the following components in parts by weight: 110 parts of polybutylene terephthalate, 20 parts of polyethylene naphthalate, 30 parts of infrared absorption masterbatch, 5 parts of antioxidant, 4 parts of ultraviolet light absorber, and 7 parts of lubricant; wherein the infrared absorption masterbatch comprises the following raw material components based on the total mass percentage of 100%: 55% polybutylene terephthalate, 15% K x WO3 and 30% modified Cs y WO3; wherein x=0.3, y=0.33.
[0053] The method for preparing the infrared absorbing film described in this embodiment comprises the following steps:
[0054] (1) 8 g of tungsten chloride and 0.1 g of potassium acetate were added to 0.55 L of ethanol, ultrasonicated and stirred until fully dissolved, reacted at 190° C. for 20 h, centrifuged after the reaction, and dried at 60° C. for 24 h to obtain the K x WO3; 100gCs y WO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 6 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 24 h to obtain the modified Cs y WO3; 6g of K x WO3, 12g modified Cs y WO3 and 22g polybutylene terephthalate are mixed evenly and then sent to a twin-screw extruder for melt extrusion granulation. The speed of the twin-screw extruder is 100r / min. The extrusion temperatures in the screws of the twin-screw extruder are: 180-190°C in zone 1, 190-210°C in zone 2, 190-210°C in zone 3, 190-210°C in zone 4, 210-230°C in zone 5, and dried at 70°C to obtain the infrared absorption masterbatch.
[0055] (2) 30 g of the infrared absorbing masterbatch described in step (1), 110 g of polybutylene terephthalate, 20 g of polyethylene naphthalate, 5 g of antioxidant, 4 g of ultraviolet light absorber, and 7 g of lubricant are mixed uniformly, sent to a twin-screw extruder for melt mixing, and extruded into a film at a temperature of 280° C. and a pressure of 6 MPa to obtain the infrared absorbing film.
[0056] Example 3
[0057] The infrared absorption film of this embodiment comprises the following components in parts by weight: 105 parts of polyethylene terephthalate, 15 parts of polyethylene naphthalate, 25 parts of infrared absorption masterbatch, 2 parts of antioxidant, 2 parts of ultraviolet light absorber, and 4 parts of lubricant; wherein the infrared absorption masterbatch comprises the following raw material components based on the total mass percentage of 100%: 75% polyethylene terephthalate, 10% K x WO3 and 15% modified Cs y WO3; wherein x=0.3, y=0.33.
[0058] The method for preparing the infrared absorbing film described in this embodiment comprises the following steps:
[0059] (1) 8 g of tungsten chloride and 0.1 g of potassium acetate were added to 0.6 L of ethanol, ultrasonicated and stirred until fully dissolved, reacted at 185° C. for 24 h, centrifuged after the reaction, and dried at 60° C. for 20 h to obtain the K x WO3; 100gCs yWO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 7.5 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 20 h to obtain the modified Cs y WO3; 6g of K x WO3,9g modified Cs y WO3 and 45g polyethylene terephthalate were mixed evenly and then sent to a twin-screw extruder for melt extrusion granulation. The speed of the twin-screw extruder was 300r / min. The extrusion temperatures in the screws of the twin-screw extruder were: 180°C in zone 1, 190°C in zone 2, 200°C in zone 3, 210°C in zone 4, 220°C in zone 5, and dried at 70°C to obtain the infrared absorbing masterbatch.
[0060] (2) 25 g of the infrared absorbing masterbatch described in step (1), 105 g of polyethylene terephthalate, 15 g of polyethylene naphthalate, 2 g of an antioxidant, 2 g of an ultraviolet light absorber, and 4 g of a lubricant are mixed uniformly, sent to a twin-screw extruder for melt mixing, and extruded into a film at a temperature of 270° C. and a pressure of 6 MPa to obtain the infrared absorbing film.
[0061] Comparative Example 1
[0062] The preparation method of the infrared absorbing film of this comparative example is the same as that of Example 1, except that the infrared absorbing masterbatch does not contain K x WO3. The specific composition and preparation method are as follows:
[0063] The infrared absorption film of this comparative example comprises the following components in parts by weight: 100 parts of polyethylene terephthalate, 10 parts of polyethylene naphthalate, 20 parts of infrared absorption masterbatch, 5 parts of antioxidant, 4 parts of ultraviolet light absorber, and 5 parts of lubricant; wherein the infrared absorption masterbatch comprises the following raw material components based on the total mass percentage of 100%: 70% polyethylene resin and 30% modified Cs y WO3; wherein y=0.33.
[0064] The method for preparing the infrared absorbing film described in this comparative example comprises the following steps:
[0065] (1) 100gCs y WO3 was added to 80 mL of ethanol and ball-milled for 2 h, 10 mL of ethanol solution containing 10 g of polyvinyl pyrrolidone was added, stirred for 1 h until uniform, and ultrasonically treated for 1 h. The dispersion after ultrasonic treatment was centrifuged and dried at 60 ° C for 24 h to obtain the modified Cs y WO3; 30g of the modified Cs yWO3 and 70g polyethylene terephthalate were mixed evenly and then sent to a twin-screw extruder for melt extrusion granulation. The speed of the twin-screw extruder was 300r / min. The extrusion temperatures in the screws of the twin-screw extruder were: 180°C in zone 1, 190°C in zone 2, 200°C in zone 3, 210°C in zone 4, 220°C in zone 5, and dried at 70°C to obtain the infrared absorbing masterbatch.
[0066] (2) Step (2) of Comparative Example 1 is consistent with step (2) of Example 1.
[0067] Comparative Example 2
[0068] The preparation method of the infrared absorbing film of this comparative example is the same as that of Example 1, except that the weight portion of the infrared absorbing masterbatch is 10 parts.
[0069] Comparative Example 3
[0070] The preparation method of the infrared absorbing film of this comparative example is the same as that of Example 1, except that the weight portion of the infrared absorbing masterbatch is 40 parts.
[0071] Comparative Example 4
[0072] The preparation method of the infrared absorbing film of this comparative example is the same as that of Example 1, except that the film does not contain polyethylene naphthalate.
[0073] Performance Testing
[0074] K obtained in Examples 1-3 of the present invention x WO3 and modified Cs y WO3 was characterized according to the following test method, and the specific characterization data are shown in Table 1.
[0075] Modified Cs y Mass proportion of polyvinyl pyrrolidone in WO3: The modified Cs y Thermal gravimetric curve of WO3 particles, calculation of modified Cs by mass loss y Mass proportion of polyvinyl pyrrolidone in WO3.
[0076] Modified Cs y WO3 particle size: Zetasizer 3000 laser particle size analyzer was used to analyze the modified Cs y The particle size of WO3 particles.
[0077] K x WO3 aspect ratio: 50 K were measured by transmission electron microscopy. x The length and diameter of WO3 particles are used to calculate the K xThe aspect ratio (length / diameter) of WO3 particles was then calculated and the average aspect ratio was obtained.
[0078] Table 1 K in Examples 1-3 x WO3 and modified Cs y Characterization data of WO3
[0079]
[0080] The infrared absorption films described in Examples 1-3 of the present invention and Comparative Examples 1-4 were subjected to performance tests according to the following test methods. The specific performance indicators are shown in Table 2.
[0081] Film thickness: tested with a thickness meter.
[0082] Thermal shrinkage: The longitudinal and transverse thermal shrinkage rates were tested using a micrometer and a blast-type constant temperature drying oven at 150°C for 30 minutes. Three samples were tested in each direction and the average value was calculated. MD represents the longitudinal direction of the film, and TD represents the transverse direction of the film.
[0083] Tensile strength: tested in accordance with GB / T 1040.3-2006.
[0084] Visible light transmittance and infrared absorptivity: Determined in accordance with GB / T2410-2008, the performance of the film was tested after 0 days and 30 days of storage. The visible light transmittance detection band is 380-780nm, and the infrared absorptivity detection band is 780-2500nm.
[0085] Table 2 Performance test data of infrared absorption films described in Examples 1-3 and Comparative Examples 1-4
[0086]
[0087] As shown in Table 2, the films of Examples 1-3 of the present invention have high visible light transmittance and infrared absorptivity; after being placed for 30 days, the visible light transmittance and infrared absorptivity still remain at a high level, indicating that the infrared absorbing film of the present invention has good stability; at the same time, the tensile strength of the film is high and the thermal shrinkage is small, indicating that the mechanical properties and heat resistance of the film are good. It can be seen from Example 1 and Comparative Example 1 that the infrared absorbing masterbatch in Comparative Example 1 does not contain K x WO3, the visible light transmittance of the obtained film is significantly reduced. It can be seen from Example 1 and Comparative Example 2 that the content of infrared light absorbing masterbatch in Comparative Example 2 is low, and the visible light transmittance and infrared absorptivity of the obtained film are greatly reduced. It can be seen from Example 1 and Comparative Example 3 that the content of infrared light absorbing masterbatch in Comparative Example 3 is high, and the visible light transmittance and infrared absorptivity of the obtained film are greatly reduced after being placed for 30 days, indicating that the K in the filmx WO3 and Cs y WO3 precipitates, thereby affecting the optical stability of the film. It can be seen from Example 1 and Comparative Example 4 that in Comparative Example 4, the film does not contain polyethylene naphthalate, and the tensile properties of the film are significantly reduced, and the thermal shrinkage rate is significantly increased.
[0088] In summary, the present invention firstly converts K x WO3 and modified Cs y WO3, and further find the optimal addition ratio of the two substances to prepare an infrared absorption masterbatch with excellent performance, and then add the masterbatch to the polyester resin and a certain amount of modified resin to obtain an infrared absorption film. The film has excellent heat resistance and mechanical properties, and can achieve maximum infrared absorption performance without sacrificing visible light transmittance, and has excellent long-term stability.
[0089] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. An infrared absorbing film, characterized in that: The invention comprises the following components by weight: 100-110 parts of polyester resin, 10-20 parts of modified resin, 20-35 parts of infrared absorbing masterbatch, and 4-17 parts of other additives; wherein the infrared absorbing masterbatch comprises the following raw material components according to the total mass percentage of 100%: 55-75% of carrier resin, 10-15% of K x WO3 and 15-30% modified CsyWO3; wherein 0<x<1, 0<y<1; the mass ratio of the KxWO3 and the modified CsyWO3 is 1:1.5-2; The carrier resin is polyethylene terephthalate; The modified resin is polyethylene naphthalate, and the intrinsic viscosity of the polyethylene naphthalate is 0.65-0.80 dL / g; The modified Cs y WO3 is Cs coated with polyvinyl pyrrolidone y WO3; the modified Cs y In WO3, the mass proportion of polyvinyl pyrrolidone is 3-5%.
2. The infrared absorbing film according to claim 1, characterized in that: The polyester resin is selected from one or more of polyethylene terephthalate, polypropylene terephthalate and polybutylene terephthalate.
3. The infrared absorbing film according to claim 1, characterized in that: The other additives include any one or more of antioxidants, ultraviolet light absorbers, and lubricants.
4. A method for preparing the infrared absorbing film according to any one of claims 1 to 3, characterized in that: The steps include: (1) Preparation of infrared absorption masterbatch: Tungsten chloride and potassium acetate were added to ethanol in a molar ratio of 2:1, ultrasonicated and stirred until fully dissolved, reacted at 180-190°C for 20-24h, and centrifuged and dried after the reaction to obtain the K x WO3; Cs y WO3 is added to ethanol for ball milling, and an ethanol solution of polyvinyl pyrrolidone is added, stirred evenly, and ultrasonically treated. The dispersion after ultrasonic treatment is centrifuged and dried to obtain the modified Cs y WO3; the K x WO3, the modified Cs y After WO3 and the carrier resin are uniformly mixed in proportion, they are sent to a twin-screw extruder for melt extrusion granulation and drying to obtain the infrared absorbing masterbatch; (2) The infrared absorbing masterbatch, polyester resin, modified resin and other additives described in step (1) are uniformly mixed in proportion, sent to a twin-screw extruder for melt mixing, and then extruded into a film to obtain the infrared absorbing film.
5. The method for preparing the infrared absorbing film according to claim 4, characterized in that: In step (1), the concentration of tungsten chloride in ethanol is 13-15 mg / mL.
6. The method for preparing the infrared absorbing film according to claim 4, characterized in that: In step (1), the Cs y The mass ratio of WO3 to polyvinyl pyrrolidone is 100:6-10.
7. The method for preparing the infrared absorbing film according to claim 4, characterized in that: In step (2), the extrusion temperature is 270-290° C., and the extrusion pressure is 4-6 MPa.
8. Use of the infrared absorbing film according to any one of claims 1 to 3 or the infrared absorbing film prepared by the preparation method according to any one of claims 4 to 7 in glass film.
Citation Information
Patent Citations
A TPU film with infrared light absorption function and its preparation method
CN108587120B
Transparent thermal insulation material and preparation method thereof
CN102643563A
Hardened flame-retardant heat-insulating master batch and production method therefor
CN110157162A